Cross‐tolerance for drought, heat and salinity stresses in chickpea (Cicer arietinum L.). (12th February 2020) - Pushpavalli, Raju; Berger, Jens D.; Turner, Neil C.; Siddique, Kadambot H. M.; Colmer, Timothy D.; Vadez, Vincent
Abstract: Chickpea crops are often exposed to a combination of drought, heat and salinity stresses during the reproductive stage. Previous efforts have largely focused on these stresses in isolation, such that we do not understand whether genotypes tolerant to one stress can withstand other stresses. Around 22–44 chickpea genotypes contrasting for tolerance to drought, salinity or heat in previous studies were exposed to terminal drought (TD, 3 experiments) and to salinity (SAL, 1 experiment). A priori stress tolerance to any of the listed stresses was generally reflected in drought and salinity tolerance in the present study. Thus, the drought‐, heat‐ and salt‐tolerant groups (DT, HT and ST) produced higher seed yield, had earlier phenology, higher harvest indices and seed yield transpiration efficiencies compared with sensitive groups (DS, HS and SS). However, tolerance did not select for prescriptive water use patterns. Despite our efforts to remove the confounding effects of phenology, 4–9 days variation in flowering time made a significant difference in productivity and differentiated tolerant from sensitive counterparts. In TD1, TD2 and SAL, all tolerant groups yielded similarly under stress conditions. This showed the existence of cross‐tolerance in chickpea where tolerant genotype selected for an individual stress can yield well under other stresses too.